Constraint of Complex Trace Analysis for Seismic Data Processing - Rahman, S. M. (Journal of Scientific Research, 2010)
Time frequency representation is a powerful tool for studying seismic reflection patterns and can thus provide useful information for stratification of the subsurface. Complex trace analysis, one of the geophysical techniques, is being employed for the time frequency analysis of seismic traces as analytic signal for the interpretation of seismic data. The applicability of the complex trace analysis in seismic data processing has been studied in this paper with few synthetic signals. The signals are analyzed with complex trace analysis for time frequency representations and compared with the spectral energy distributions. It is shown that complex trace analysis is not suitable for accurate estimation of time frequency representation of the signals having simultaneous frequencies. Keywords: Time frequency; Complex trace; Analytic signal; Spectral analysis. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.2106 J. Sci. Res. 3 (1), 65-73 (2011)